Persepsi Guru Bahasa Indonesia terhadap Full Day School - Safi'i, Imam; Warni, Silih; Yanti, Prima Gusti (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2020)
This study aims to describe the relationship between employment status and employment to the perceptions of Indonesian teachers about the discourse of the implementation of full day school system. The data in this study was collected online with media questionnaires developed through googleform. The data collected is further processed using regression analysis method with SPSS to see the existence of relationship or relationship between variables. The result of the research shows that there is a relationship between employment status and work period to the perception of Indonesian teachers about the discourse of the implementation of full day school system. Based on the SPSS output results in the summary model table the value of "R" is 0.096 and 0.123 respectively. The results of this research can be used as one of the starting point to conduct a more comprehensive study related to the implementation of full day scholl system in the school system in Indonesia.